Posterior scleritis with choroidal detachments and periaortitis associated with IgG4-related disease: A case report. Issue 29 (22nd July 2022) - Mase, Yoko; Kubo, Akiko; Matsumoto, Akane; Masuda, Kosuke; Kadoya, Masatoshi; Koizumi, Kan; Sotozono, Chie; Kondo, Mineo
Abstract : Background: IgG4-related diseases (IgG4-RDs) are known to disrupt the functioning of multiple organs and are usually associated with mass lesions. Periaortitis, an inflammation of the adventitia and tissues surrounding the aorta, is an example of an IgG4-RD. In ophthalmology, an enlargement of the lacrimal gland is a well-known IgG4-RD, and scleritis has also been reported to be an IgG4-RD although it is rare. We report our findings in a case with periaortitis and posterior scleritis that were present at the same time, and they responded well to systemic steroid therapy. Patients concerns: A 79-year-old man with dementia and Lewy bodies was referred to our hospital because of uveitis in both eyes that did not respond to topical steroid therapy. Diagnosis: We found anterior scleritis in the right eye and uveitis with shallow anterior chambers in both eyes. B-mode echography showed choroidal detachments (CDs) and a T sign in the right eye. The CDs were assumed to have progressed to the posterior scleritis which then caused the severe vision reduction. The patient was referred to the Internal Medicine Department because the systemic inflammatory disease was suspected due to the high levels of C-reactive protein (CRP) and the fast erythrocyte sedimentation rate. Systemic CT scans showed periaortitis only at the lumbar region. Because of the high levels of IgG4, the patient was diagnosed with IgG4-RD. Interventions: The patient received intravenous and oral steroid therapy. The first 125 mg of methylprednisolone (mPSL) for 3 days was intravenous, after which it was switched to oral prednisolone (PSL) therapy and the dosage was gradually reduced. Outcomes: The posterior scleritis and periaortitis responded well to the systemic steroid therapy. One year and a half after the onset of the disease, the patient is still taking 5 mg of PSL. Conclusions: Scleritis with multiple CDs and periaortitis were strongly suspected to be due to IgG4-RD although no definitive diagnosis was made by biopsy of the lesions. Clinicians should be aware that IgG4-RD should be considered as one of the causes of posterior scleritis.